RELATIONSHIP BETWEEN DOMESTIC AND INTERNATIONAL LAW ACCORDING TO THE CONSTITUTION OF MONTENEGRO: GENERAL OVERVIEW OF THE RELATIONSHIP BETWEEN DOMESTIC AND INTERNATIONAL LAW - Rajović, Miloš (Glasnik Advokatske komore Vojvodine, 2022)
The relationship between domestic (state) law, or more precisely domestic laws, and international law is one of the most complex and dynamic issues, both in foro interno and  in foro externo, resulting in different and numerous theoretical and practical solutions. Through basic theoretical starting points (monism and dualism), through comparative constitutional practice, the paper seeks to provide a detailed analysis of the provisions of the Constitution of Montenegro from 2007 concerning the relationship between domestic and international law, especially Article 9. Opting for a monistic approach with relative With the primacy of international law, the Montenegrin Constitution prescribes that international treaties and generally accepted rules of international law are an integral part of the internal order. The analysis of the Constitution in the manner of de lege lata pointed out some basic errors and shortcomings of the positive legal solution of the relationship between domestic and international law limited by Article 9., and resulted in a proposed correction in the manner of de lege ferenda, all in order to reduce potential international legal responsibility of Montenegro.
Keywords: Internal law; International law; Monism, Constitution of Montenegro; Article 9 of the Constitution.